Effect of nutritional support in patients with lower respiratory tract infection: Secondary analysis of a randomized clinical trial. Issue 4 (April 2021) - Baumgartner, Annic; Hasenboehler, Flavia; Cantone, Jennifer; Hersberger, Lara; Bargetzi, Annika; Bargetzi, Laura; Kaegi-Braun, Nina; Tribolet, Pascal; Gomes, Filomena; Hoess, Claus; Pavlicek, Vojtech; Bilz, Stefan; et al.
Summary: Background: In polymorbid patients with bronchopulmonary infection, malnutrition is an independent risk factor for mortality. There is a lack of interventional data investigating whether providing nutritional support during the hospital stay in patients at risk for malnutrition presenting with lower respiratory tract infection lowers mortality. Methods: For this secondary analysis of a randomized clinical trial (EFFORT), we analyzed data of a subgroup of patients with confirmed lower respiratory tract infection from an initial cohort of 2028 patients. Patients at nutritional risk (Nutritional Risk Screening [NRS] score ≥3 points) were randomized to receive protocol-guided individualized nutritional support to reach protein and energy goals (intervention group) or standard hospital food (control group). The primary endpoint of this analysis was all-cause 30-day mortality. Results: We included 378 of 2028 EFFORT patients (mean age 74.4 years, 24% with COPD) into this analysis. Compared to usual care hospital nutrition, individualized nutritional support to reach caloric and protein goals showed a similar beneficial effect of on the risk of mortality in the subgroup of respiratory tract infection patients as compared to the main EFFORT trial (odds ratio 0.47 [95%CI 0.17 to 1.27, p = 0.136] vs 0.65 [95%CI 0.47 to 0.91, p = 0.011]) with no evidence of a subgroup effect (p for interaction 0.859). Effects were also similar among different subgroups based on etiology and type of respiratory tract infection and for other secondary endpoints. Conclusion: This subgroup analysis from a large nutrition support trial suggests that patients at nutritional risk as assessed by NRS 2002 presenting with bronchopulmonary infection to the hospital likely have a mortality benefit from individualized inhospital nutritional support. The small sample size and limited statistical power calls for larger nutritional studies focusing on this highly vulnerable patient population. Clinical trial registration: Registered under ClinicalTrials.gov Identifier no. NCT02517476.